The Transcription-Repair Coupling Factor Mfd Prevents and Promotes Mutagenesis in a Context-Dependent Manner - Lindsey-Boltz, Laura A.; Sancar, Aziz (Frontiers in Molecular Biosciences, 2021)
The mfd (mutation frequency decline) gene was identified by screening an auxotrophic Escherichia coli strain exposed to UV and held in a minimum medium before plating onto rich or minimal agar plates. It was found that under these conditions, holding cells in minimal (non-growth) conditions resulted in mutations that enabled cells to grow on minimal media. Using this observation as a starting point, a mutant was isolated that failed to mutate to autotrophy under the proscribed conditions, and the gene responsible for this phenomenon (mutation frequency decline) was named mfd. Later work revealed that mfd encoded a translocase that recognizes RNA Polymerase (RNAP) stalled at damage sites and binds to the stalled RNAP, recruits the nucleotide excision repair damage recognition complex UvrA2UvrB to the site, and facilitates damage recognition and repair while dissociating the stalled RNAP from the DNA along with the truncated RNA. Recent single molecule and genome-wide repair studies have revealed time-resolved features and structural aspects of this transcription-coupled repair (TCR) phenomenon. Interestingly, recent work has shown that in certain bacterial species Mfd also plays roles in recombination, bacterial virulence, and development of drug resistance.